Long Distance Marriage Couple Communication Pattern during the Covid-19 Pandemic - Yani Tri Wijayanti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
The Covid-19 pandemic in Indonesia, made the government take steps to reduce the spread of the virus by making health protocols, restricting activities outsides the home, and the travel ban. This impact is strongly felt by long distance marriage (LDM) couples. LDM couples are committed by husband and wife who do not live together because of work demands. The communication is long distance using the media. The purpose of this study is to find out and analyze patterns of family communication in LDM couples during the Covid-19 pandemic. The method used is a case study, selection of research informants using purposive sampling techniques and data collection with in-depth interviews. Family communication patterns are formed from factors that influence, form of communication and quality of communication. When the Covid-19 pandemic intensity of family communication in LDM couples increased using media such as telephone, chat and video calls.